Doppler spectra of medium grazing angle sea clutter; part 1: characterisation. Issue 1 (1st January 2016) - Watts, Simon; Rosenberg, Luke; Bocquet, Stephen; Ritchie, Matthew
Abstract : This study is concerned with the characterisation of Doppler spectra from high range resolution X‐band radar sea clutter observed from an airborne platform over the range of grazing angles, 15° to 45°. It is observed that when looking up or down wind there is a strong correlation between mean Doppler shift and local spectrum intensity. When combined with random fluctuations of spectrum width, these characteristics give the spectra a temporal and spatial variability. This behaviour has previously been observed in low grazing angle data and these results confirm the wider applicability of the models developed using that data. The modelling method is also extended here to capture the bimodal behaviour observed with high intensity returns from breaking waves looking up or down‐wind.